The Development of Motion-Based Individual Badminton Smash Forehand Training Models for Students of IKIP Mataram 2019 - Soemardiawan, Soemardiawan; Tangkudung, James; Hanif, Ahmad Sofyan (Universitas Malikussaleh, 2019)
This article produces a product in the form of an individual smash training model to improve the forehand smash capability which is based on good motion, has advantages over the previous model, where the model of individual smash forehand variations is to improve motion-based badminton Smash Skills. The aim to be achieved in development research is to produce a product program for individual smash forehand training which is efficiently and effectively varied, and also improve smash forehand skills, both in motion, technical skills, individually in the IKIP Mataram students. The population and samples using NTB athletes belonging to the UKM FPOK IKIP Mataram were 100 students. The instruments used in this development research were questionnaires, questionnaires, and the Badminton Smash Test Instrument from Purnama. The design of this study uses the research & development (R & D) development method of Borg and Gall which is qualitative in nature and while the quantitative approach is used to reveal the second objective, with a pre-experimental research design in the form of the one group pretest-posttest design. who looked for significant differences in individual forehand smash models before and after training were given a smash model. Based on the analysis of research data using the t test with a significance level of 0.05. Therefore, the research on the development of individual forehand smash models based on the results of badminton training from the results of research shows that the use of a varied and effective forehand smash training model can improve this forehand smash training model for badminton athletes in IKIP Mataram students.